Nb-Ce doped silicon carbide ceramic membrane and preparation method and application thereof

CN123003293APending Publication Date: 2026-10-30NINGXIA UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611526390.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本申请要解决的问题是现有陶瓷膜催化活性组分与基体结合力弱、催化稳定性差,以及臭氧催化氧化陶瓷膜中催化活性组分多为单一金属氧化物,活性位点类型单一,吸附与氧化缺乏协同,臭氧利用率及污染物矿化效率不足

Benefits of technology

1.本申请通过铈的氧化物与铌的氧化物在烧结过程中的原位固相反应生成含铈和铌的复合氧化物相,含铈和铌的复合氧化物相分布于碳化硅基体的颗粒表面及颗粒颈部区域,复合氧化物相与碳化硅基体之间形成化学键合,结合牢固,缓解了物理负载方式中催化组分易脱落流失的缺陷,催化稳定性提高。含铈和铌的复合氧化物相形成的富含活性位点的催化层,膜中同时存在Ce3+/Ce4+氧化还原对、丰富的氧空位及表面酸性位点,构成多活性位点协同体系,Ce3+/Ce4+循环活化臭氧产生·OH和·O2-等活性氧物种,表面酸性位点吸附富集有机污染物,两者协同为有机污染物的高效降解提供强氧化驱动力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003293A_ABST
    Figure CN123003293A_ABST
Patent Text Reader

Abstract

The application provides an Nb-Ce doped silicon carbide ceramic film and a preparation method and application thereof. The method comprises the following steps: mixing oxide powder of cerium and oxide powder of niobium with silicon carbide powder to obtain mixed powder; forming the mixed powder into a film blank; and sintering the film blank at 1050-1200 DEG C under an air atmosphere, so that the oxide of cerium and the oxide of niobium are doped in the silicon carbide substrate in situ and a composite oxide phase containing cerium and niobium is generated in situ, and meanwhile the composite oxide phase containing cerium and niobium generates surface oxygen vacancies at the sintering temperature, thereby obtaining the Nb-Ce doped silicon carbide ceramic film. The Nb-Ce doped silicon carbide ceramic film has good ozone catalytic oxidation performance and can realize efficient degradation of high-concentration organic wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of inorganic membrane materials technology, specifically to an Nb-Ce doped silicon carbide ceramic membrane, its preparation method, and its application. Background Technology

[0002] Combining ozone catalytic oxidation with ceramic membrane separation technology to form a catalytic ozone oxidation ceramic membrane process has become a research hotspot in the field of wastewater treatment in recent years. This process organically combines the physical separation effect of ceramic membrane with the ozone-driven chemical oxidation effect. It can not only reduce the size of ozone bubbles and enhance gas-liquid mass transfer through the shearing effect of the membrane surface, but also load the catalyst on the surface of the ceramic membrane or inside the membrane pores, eliminating the need for subsequent catalyst separation and recovery. Moreover, the ozone catalytic oxidation effect can effectively degrade organic pollutants on the membrane surface and mitigate membrane fouling.

[0003] Silicon carbide (SiC) ceramic membranes are considered ideal substrate materials for ozone catalytic oxidation due to their excellent chemical stability, high temperature resistance, and high mechanical strength. However, the high chemical inertness and lack of catalytic active sites on the surface of SiC ceramic membranes limit their direct application in catalytic ozone oxidation. To impart catalytic activity to SiC ceramic membranes, existing technologies typically employ a strategy of loading metal oxide catalytic components onto the surface or within the pores of the SiC membrane. However, in such physical coating or impregnation loading methods, the catalytic active component and the ceramic matrix only undergo physical adsorption or weak mechanical intercalation, resulting in limited bonding strength. Under long-term operation and hydraulic scouring conditions, the active component is prone to detachment and loss, leading to insufficient catalytic stability.

[0004] To improve the bonding strength between the catalytic component and the substrate, some studies have explored a strategy of integrating metal oxides with SiC through co-sintering. This allows the metal oxides to be attached to the surface of SiC particles in the form of sintered necks, achieving a chemical bond between the catalytic active phase and the membrane substrate. Chinese patent application CN119306314A discloses a silicon carbide microreactor for ozone catalysis and its preparation method, using SiC as the substrate and metal oxides as the catalytic active component. The metal oxides are attached to the surface of SiC particles in the form of sintered necks for ozone catalytic oxidation of wastewater treatment. This scheme establishes a technical route of "SiC + metal oxide sintered neck + ozone catalysis," but the metal oxides involved are a single component with a single type of active site, lacking the ability to adsorb and enrich organic pollutants. There is also a lack of a synergistic mechanism between adsorption and oxidation, resulting in limited ozone utilization and pollutant mineralization efficiency.

[0005] Chinese patent application CN112979282A discloses an alumina ceramic sintered body and its preparation method. This patent uses α-Al₂O₃ particles as the matrix and Ce₂O₃ and Nb₂O₅ as additives. During sintering, Ce₂O₃ reacts with Nb₂O₅ to generate CeNbO₄ as a liquid phase, lowering the sintering temperature and promoting the anisotropic growth of Al₂O₃ grains into columnar crystals. Toughening is achieved through the crack deflection and pull-out effect of the columnar crystals. However, the technical objective of this patent document is to improve fracture toughness through liquid-phase sintering. CeNbO₄ is only used as a liquid-phase sintering aid. In this patent document, CeNbO₄ is generated based on the liquid-phase reaction system of Ce₂O₃ and Nb₂O₅. CeNbO₄ fills the intergranular spaces of Al₂O₃ in a molten state at high temperature and crystallizes into a grain boundary phase after cooling, failing to construct CeNbO₄. 3+ / Ce 4+ Redox pairs and surface oxygen vacancies. Summary of the Invention

[0006] The problems to be solved by this application are: weak bonding between the active components of existing ceramic membranes and the substrate, poor catalytic stability, and the fact that the active components in ozone catalytic oxidation ceramic membranes are mostly single metal oxides with a single type of active site, lack of synergy between adsorption and oxidation, and insufficient ozone utilization and pollutant mineralization efficiency.

[0007] To address the aforementioned problems, the first aspect of this application provides an Nb-Ce-doped silicon carbide ceramic film. The Nb-Ce-doped silicon carbide ceramic film uses silicon carbide as a substrate. The bulk phase of the substrate contains a cerium- and niobium-containing composite oxide phase formed by an in-situ solid-state reaction of cerium oxide and niobium oxide. The surface of the Nb-Ce-doped silicon carbide ceramic film has Ce... 3+ / Ce 4+ Redox pairs and oxygen vacancies.

[0008] Furthermore, the cerium- and niobium-containing composite oxide phase is a CeNbO4 composite oxide phase.

[0009] Furthermore, the cerium- and niobium-containing composite oxide phase is distributed on the particle surface and in the particle neck region of the silicon carbide matrix.

[0010] The second aspect of this application also provides a method for preparing an Nb-Ce-doped silicon carbide ceramic film, comprising the following steps: mixing cerium oxide powder and niobium oxide powder with silicon carbide powder to obtain a mixed powder; forming the mixed powder into a film preform; sintering the film preform at 1050-1200℃ in an oxidizing atmosphere, so that cerium oxide and niobium oxide are in situ doped into the silicon carbide matrix and a cerium- and niobium-containing composite oxide phase is generated in situ, while the cerium- and niobium-containing composite oxide phase generates surface oxygen vacancies at the sintering temperature, thereby obtaining an Nb-Ce-doped silicon carbide ceramic film.

[0011] Furthermore, the mixed powder also contains a pore-forming agent and a low-temperature binder.

[0012] Furthermore, the cerium oxide powder is cerium oxide, and the niobium oxide powder is niobium oxide.

[0013] Furthermore, the mass ratio of cerium oxide powder to niobium oxide powder is (1.5-2.5):1.

[0014] Furthermore, the step of forming the mixed powder into a preform includes adding plasticizer and solvent to the mixed powder, kneading it evenly, and then aging and extruding it to obtain a tubular preform.

[0015] Furthermore, the oxidizing atmosphere is an air atmosphere.

[0016] The third aspect of this application also provides the application of the above-mentioned Nb-Ce doped silicon carbide ceramic membrane in the ozone catalytic oxidation degradation of organic wastewater.

[0017] The technical advantages of this application are as follows: 1. This application utilizes an in-situ solid-state reaction between cerium oxide and niobium oxide during sintering to generate a cerium- and niobium-containing composite oxide phase. This composite oxide phase is distributed on the particle surface and neck region of the silicon carbide matrix. The composite oxide phase forms a strong chemical bond with the silicon carbide matrix, mitigating the drawback of easy catalytic component detachment and loss in physical loading methods, thus improving catalytic stability. The catalytic layer formed by the cerium- and niobium-containing composite oxide phase is rich in active sites, and Ce is present in the film simultaneously. 3+ / Ce 4+ Redox pairs, abundant oxygen vacancies, and surface acidic sites constitute a multi-active-site synergistic system, Ce 3+ / Ce 4+ The cyclic activation of ozone produces ·OH and ·O2. - These reactive oxygen species, along with their acidic surface sites, adsorb and enrich organic pollutants, working synergistically to provide a strong oxidative driving force for the efficient degradation of organic pollutants.

[0018] 2. In this application, cerium oxide provides redox active sites, niobium oxide provides acidic adsorption sites, and the CeNbO4 composite oxide phase has both redox and acidic adsorption functions. The coexistence of the three phases constitutes a synergistic catalytic system, which can simultaneously achieve physical retention and chemical degradation of pollutants and alleviate membrane fouling. The membrane has good anti-interference ability against common coexisting ions in water and is suitable for the efficient treatment of organic wastewater under complex water quality conditions.

[0019] 3. This application uses a cerium oxide and niobium oxide composite as a two-component catalytic system, which is introduced into a silicon carbide ceramic membrane via in-situ doping. The preparation process is simple, short-cycle, and requires no additional loading steps. The catalyst and membrane substrate form a strong chemical bond through sintering, which is not easily detached during long-term operation. One-step sintering at 1050-1200℃ under an oxidizing atmosphere is used to simultaneously generate the composite oxide phase and construct Ce in situ. 3+ / Ce 4+ Redox pairs and oxygen vacancies require no additional reduction treatment or loading process, making the process simple, with a short preparation cycle, and suitable for large-scale production. Attached Figure Description

[0020] Figure 1 This is a scanning electron microscope image of the Nb-Ce-doped silicon carbide ceramic film prepared in Example 1 of this application; Figure 2 The image shows the X-ray photoelectron spectroscopy (XPS) spectrum of the Nb-Ce-doped silicon carbide ceramic film prepared in Example 1 of this application. Figure 3 The electron spin resonance (ESR) spectrum of the Nb-Ce-doped silicon carbide ceramic film prepared in Example 1 of this application is shown. Figure 4 The pore size distribution diagram is shown for the Nb-Ce-doped silicon carbide ceramic film prepared in Example 1 of this application. Figure 5 The X-ray diffraction patterns of the Nb-Ce-doped silicon carbide ceramic films in Examples 1, 2 and Comparative Example 3 of this application are shown. Figure 6 This is a performance diagram of the ozone catalytic oxidation of ciprofloxacin wastewater by the Nb-Ce-doped silicon carbide ceramic membrane prepared in Example 1 of this application; Figure 7 The image shows the performance of the Nb-Ce-doped silicon carbide ceramic membrane prepared in Example 1 of this application for ozone catalytic oxidation of methylene blue wastewater. Detailed Implementation

[0021] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.

[0022] The embodiments of this application first provide an Nb-Ce-doped silicon carbide ceramic film. The Nb-Ce-doped silicon carbide ceramic film uses silicon carbide as a substrate. The bulk phase of the substrate contains a cerium- and niobium-containing composite oxide phase formed by an in-situ solid-state reaction of cerium oxide and niobium oxide. The surface of the Nb-Ce-doped silicon carbide ceramic film has Ce... 3+ / Ce 4+ Redox pairs and oxygen vacancies.

[0023] The Nb-Ce doped silicon carbide ceramic film uses silicon carbide (SiC) ceramic as the substrate. The silicon carbide ceramic substrate has a porous structure with interconnected channels and pores. The bulk phase of the substrate contains a composite oxide phase of cerium and niobium. This composite oxide phase is generated by an in-situ solid-state reaction between cerium oxide and niobium oxide; that is, the cerium- and niobium-containing composite oxide phase is generated in situ during sintering through a solid-state reaction under solid-state conditions, rather than being added externally after pre-synthesis. This in-situ solid-state reaction results in a strong chemical bond between the composite oxide phase and the silicon carbide substrate.

[0024] Among them, cerium oxides include, but are not limited to, CeO2, Ce2O3 and CeO 2-x One or more of the following (0 < x < 0.5): CeO2 is a stable +4 valence oxide of cerium; Ce2O3 is easily oxidized to CeO2 in air; CeO... 2-x It is an oxygen-deficient solid solution, with some Ce in its crystal structure. 4+ With Ce 3+ The cerium oxide exists in its original form and is associated with the generation of oxygen vacancies, playing a central role in the catalytic redox cycle. Under the oxidizing atmosphere sintering conditions of this application, the aforementioned cerium oxides ultimately exist in the ceramic film in the forms of CeO2 and CeNbO4. In the following embodiments, the cerium oxide is preferably CeO2. Niobium oxides include, but are not limited to, one or more of Nb2O5, NbO2, NbO, and Nb2O3. Among them, Nb2O5 is the most chemically stable; NbO2 and Nb2O3 can be oxidized to Nb2O5 in air, respectively. Under the oxidizing atmosphere sintering conditions of this application, the aforementioned niobium oxides ultimately exist in the ceramic film in the forms of Nb2O5 and CeNbO4. In the following embodiments, the niobium oxide is preferably Nb2O5.

[0025] In Nb-Ce-doped silicon carbide ceramic films, the cerium- and niobium-containing composite oxide phase is mainly CeNbO4 composite oxide phase. The CeNbO4 composite oxide phase is distributed on the particle surface and in the particle neck region of the silicon carbide matrix. The particle neck region refers to the contact connection area between adjacent silicon carbide particles, which is an important part of the film pore structure. The concentration of the CeNbO4 composite oxide phase in this region ensures that the catalytic active sites are distributed on the surface of the film pores and in the key channels of gas-liquid mass transfer, which is beneficial to the full catalytic reaction. Under the above sintering conditions, CeO2 and Nb2O5 undergo a solid-state reaction to generate the CeNbO4 composite oxide phase, in which Ce changes from +4 to +3 valence, while Nb remains at +5 valence, forming the crystal structure of CeNbO4 (cerium (III) niobate).

[0026] The surface of the ceramic film has Ce 3+ / Ce 4+Redox pairs and oxygen vacancies. Ce 3+ / Ce 4+ Redox pairs refer to the simultaneous presence of Ce on the surface of a ceramic film. 3+ and Ce 4+ Cerium ions in two valence states can achieve catalytic function through a reversible redox cycle. Oxygen vacancies refer to defect sites formed by the absence of oxygen atoms in the ceramic film lattice. Ce 3+ / Ce 4+ Redox pairs and oxygen vacancies together constitute redox active centers, which can activate ozone molecules to produce hydroxyl radicals (·OH) and superoxide radicals (·O2). - (and other reactive oxygen species)

[0027] This application also provides a method for preparing the above-mentioned Nb-Ce-doped silicon carbide ceramic film. A method for preparing an Nb-Ce-doped silicon carbide ceramic film specifically includes the following steps: Step 1: Weigh out cerium oxide powder, niobium oxide powder and silicon carbide powder in a ratio of (1-3):(1-3):(20-22) and mix them evenly in a kneader to obtain powder.

[0028] In some embodiments, the oxide of cerium is selected as cerium oxide (CeO2), and the oxide of niobium is selected as niobium oxide (Nb2O5). The mass ratio of CeO2 powder to Nb2O5 powder is (1.5-2.5):1. Within this mass ratio range, it is beneficial for CeO2 and Nb2O5 to react fully to form a CeNbO4 composite oxide phase, while retaining an appropriate amount of free CeO2 and Nb2O5. This results in the simultaneous presence of the CeNbO4 composite phase, the CeO2 redox active component, and the Nb2O5 acidic adsorption component in the membrane, with the three phases coexisting to form a synergistic catalytic system.

[0029] In some embodiments, the mixed powder also includes a pore-forming agent and a low-temperature binder. The pore-forming agent burns and volatilizes during sintering to form a membrane pore structure, while the low-temperature binder promotes neck sintering between SiC particles. The pore-forming agent can be selected from one or more of starch, wood flour, and ammonium bicarbonate. The low-temperature binder can be selected from one or more of clay, bentonite, and low-melting-point glass powder.

[0030] Step 2: Add the plasticizer and deionized water to the powder obtained in Step 1 and continue to knead evenly to obtain a paste-like slurry. The plasticizer can be selected from one or more of soybean oil, glycerin, polyethylene glycol, and polyvinyl butyral. The solvent can be selected from one or both of deionized water and anhydrous ethanol.

[0031] Step 3: Place the paste-like sludge from Step 2 into the reactor and age it for 20-30 hours; Step 4: Place the aged mud from Step 3 into a vacuum mud refiner for refining. After eliminating air bubbles, place it again into a reaction vessel for secondary aging for 20-30 hours. Step 5: Place the sludge after secondary aging in Step 4 into the inner cavity of the extruder and extrude it under an axial pressure of 5-15 MPa to obtain a tubular wet preform. Then, place it at room temperature for 2-3 days to form a film preform. The time from wet preform to film preform should not be less than 48 hours. The shape of the film preform can also be flat or porous honeycomb.

[0032] Step 6: Place the preform in a muffle furnace and heat it to 1050-1200℃ in air atmosphere at a rate of 2-5℃ / min. Hold the temperature for 2-4 hours to form the preform. After cooling, ultrasonically clean it for 10-30 minutes to remove any loose particles remaining on the surface of the film. Then dry it to obtain the Nb-Ce doped silicon carbide ceramic film.

[0033] During sintering, the following in-situ reactions occur: (1) CeO2 and Nb2O5 undergo in-situ solid-state reaction on the surface and neck region of SiC particles to generate CeNbO4 composite oxide phase; (2) Under sintering conditions of 1050-1200℃, surface oxygen vacancies are generated; (3) Porous framework structure is formed between SiC particles through neck sintering. The above three processes are carried out simultaneously in the temperature range of 1050-1200℃ and completed in one step. Sintering temperature has an important influence on the generation of CeNbO4 composite oxide phase and the integrity of film structure. When the sintering temperature is below 1050℃, the driving force for solid-state diffusion between cerium oxide and niobium oxide is insufficient, the generation of CeNbO4 composite oxide phase is limited, and the film blank is not fully sintered and densified, resulting in insufficient mechanical strength; when the sintering temperature is above 1200℃, the SiC matrix undergoes excessive oxidation, SiC is converted into SiO2, leading to the collapse of the film pore structure and a decrease in mechanical strength.

[0034] The implementation methods of this application are further illustrated below through specific examples and comparative examples.

[0035] Example 1 The preparation of Nb-Ce doped silicon carbide ceramic films in this application.

[0036] Step 1: Place 100g of cerium oxide powder, 50g of niobium oxide powder, 1050g of silicon carbide powder, 150g of pore-forming agent, and 120g of low-temperature binder into a kneader and mix evenly. Step 2: Weigh 75g of soybean oil, 75g of glycerin and 367g of deionized water and add them to the kneader to continue kneading until a paste-like mud is obtained; Step 3: Place in a reaction vessel and age for 30 hours; Step 4: Place the aged mud into a vacuum mud refining machine for refining, and after eliminating air bubbles, place it again in a reaction kettle for secondary aging for 20 hours. Step 5: Place the sludge after secondary aging into the inner cavity of the extruder and extrude it under an axial pressure of 10MPa to obtain a tubular wet preform with an outer diameter of 12mm and an inner diameter of 8mm. Dry it at room temperature for 48h to obtain a film preform. Step 6: Place the preform in a muffle furnace and heat it to 1150℃ at 2℃ / min in an air atmosphere. Hold the temperature for 2 hours to form the preform. After cooling, clean it ultrasonically for 10-30 minutes. Finally, dry it at 120℃ for 2 hours to obtain the Nb-Ce doped silicon carbide ceramic film.

[0037] Example 2 The only difference between this embodiment and Embodiment 1 is that in step 6, the temperature is increased to 1050°C at a rate of 2°C / min in an air atmosphere. All other steps and parameters are the same as in Embodiment 1.

[0038] Comparative Example 1 The only difference between this comparative example and Example 1 is that, in step 1, niobium oxide powder is not added; instead, 150g of cerium oxide powder (the same total amount of cerium oxide and niobium oxide powder as in Example 1) is mixed with 1050g of silicon carbide powder and sintered. All other steps and parameters are the same as in Example 1.

[0039] Comparative Example 2 The only difference between this comparative example and Example 1 is that, in step 1, cerium oxide powder is not added; instead, 150g of niobium oxide powder (the same total amount of cerium oxide and niobium oxide powder as in Example 1) is mixed with 1050g of silicon carbide powder and sintered. All other steps and parameters are the same as in Example 1.

[0040] Comparative Example 3 The only difference between this comparative example and Example 1 is that in step 6, the temperature is increased to 1250°C at a rate of 2°C / min in air. All other steps and parameters are the same as in Example 1.

[0041] Comparative Example 4 The only difference between this comparative example and Example 1 is that in step 6, the temperature is increased to 900°C at a rate of 2°C / min in air. All other steps and parameters are the same as in Example 1.

[0042] The Nb-Ce-doped silicon carbide ceramic membrane prepared in Example 1 was characterized, and the average pore size was found to be 1.13 μm, the porosity to be 46.62%, the flexural strength to be 54.17 MPa, and the pure water flux to be 121767 L·m. -2 ·h -1 ·bar -1 .

[0043] The average pore size was determined using the nitrogen bubbling method (PSDA-30 pore size analyzer). Before testing, the membrane was vacuum-wetted with ethanol for 15 minutes. Porosity was calculated using the deionized water hydrostatic weighing method based on Archimedes' principle, with P = (m1-m2) / (m1-m3) × 100%, where m1, m2, and m3 represent the mass of the ceramic membrane in air after water saturation, the mass in air after drying, and the suspended mass in water after water saturation, respectively. Bending strength was determined using the three-point bending method (HYZ-LL-2T universal tensile testing machine), with a lower support blade spacing of 90 mm and an upper indenter pressure of 0.5 mm·min. -1 When pressure is applied until fracture, the flexural strength is calculated as σ = 8PL(d + 2S) / [π((d + 2S)]. 4 -d 4 The calculation is as follows: P(N) is the fracture load, L(mm) is the distance between the lower support blades, d(mm) is the inner diameter at the fracture, and S(mm) is the wall thickness at fracture. A tubular cross-flow filtration device is used with deionized water as the feed liquid to determine the pure water flux. The pure water permeability is calculated according to J=V / (A·Δt·Δp), where V is the permeate volume (L) and A is the effective filtration area of ​​the membrane (m²). 2 ), t is the test time (h), and ΔP is the transmembrane pressure difference (bar).

[0044] Figure 1 The image shows a scanning electron microscope (SEM) image of the Nb-Ce-doped silicon carbide ceramic film prepared in Example 1. The SEM image reveals that the Nb-Ce-doped silicon carbide ceramic film prepared in Example 1 has fine particulate matter distributed on the surface of the SiC particles and in their neck regions. These catalytic particles are uniformly anchored to the surface of the SiC aggregate, rather than simply adhering. During sintering, CeO2 and Nb2O5 powders are sintered simultaneously with the SiC particles. The catalytically active components are embedded into the neck regions between the SiC particles through solid-phase reactions, forming an integrated structure of the catalytic layer and the membrane substrate. There is no obvious physical interface between the catalytic layer and the membrane substrate; instead, they are firmly anchored through chemical bonding at the sintered neck, forming a catalytic layer rich in active sites. This endows the catalytic membrane with good mechanical stability and long-term operational reliability, improving ozone catalytic efficiency.

[0045] Figure 2 The image shows the X-ray photoelectron spectroscopy (XPS) spectrum of the Nb-Ce-doped silicon carbide ceramic film prepared in Example 1. The Ce3d spectrum indicates that Ce is present on the surface of the ceramic film. 3+ and Ce 4+ The characteristic peaks indicate that Ce exists on the ceramic film surface in both +3 and +4 valence states, where Ce... 3+ Derived from CeNbO4 composite oxide phase, Ce 4+ CeO2 originates from unreacted free CeO2, and the two coexist to form Ce. 3+ / Ce4+ Redox pairs. The O 1s spectrum reveals the simultaneous presence of lattice oxygen and surface-adsorbed oxygen / oxygen vacancy-related oxygen on the ceramic film surface. The appearance of the oxygen vacancy-related oxygen peak directly confirms the presence of oxygen vacancies. Some oxygen atoms in the lattice are released to form oxygen vacancies, which interact with Ce. 3+ / Ce 4+ Redox pairs together constitute the redox active centers on the membrane surface.

[0046] Figure 3 The image shows the electron spin resonance (ESR) spectrum of the Nb-Ce-doped silicon carbide ceramic film prepared in Example 1. The ESR spectrum reveals a distinct characteristic signal peak at approximately g=2.004, which is attributed to the Fo electrons trapped by oxygen vacancies. + The presence of color centers further confirmed the existence of oxygen vacancies on the ceramic film surface. The ESR results and XPS analysis of the O 1s spectrum corroborated each other, jointly demonstrating the abundant oxygen vacancy defects on the surface of the Nb-Ce-doped silicon carbide ceramic film. These oxygen vacancies can serve as adsorption activation sites for ozone molecules, promoting the adsorption and dissociation of O3 on the catalyst surface, generating ·OH and ·O2. - Reactive oxygen species, etc.

[0047] Figure 4 The image shows the pore size distribution of the Nb-Ce-doped silicon carbide ceramic film prepared in Example 1. The pore size distribution is concentrated in the range of 0.5–3.0 μm, with an average pore size of 1.13 μm and a porosity of 46.62%, forming a predominantly micron-sized interconnected pore structure. The CeNbO4 composite oxide phase is distributed on the surface of the SiC particles and in the particle neck region, precisely located in a crucial position on the inner wall of the pores. This provides ample conditions for ozone bubble breakage, mass transfer of organic pollutants, and contact with catalytically active sites, thus facilitating the full catalytic reaction.

[0048] Figure 5The X-ray diffraction patterns are shown for Examples 1, 2, and Comparative Example 3. At a sintering temperature of 1050℃, characteristic peaks of SiO2 and CeO2, as well as diffraction signals of Nb2O5, were detected, indicating that Ce and Nb components are mainly dispersed in the SiC matrix as their respective single oxide forms. As the sintering temperature increased to 1150℃, the intensity of the characteristic peaks of CeO2 and Nb2O5 changed. Simultaneously, new diffraction peaks matching the CeNbO4 standard card appeared at some diffraction angle positions. The intensity of the CeNbO4 diffraction peak continued to increase, indicating that the solid-state reaction proceeded gradually, and the crystallinity of the composite oxide phase improved with increasing temperature. When the temperature was further increased to 1250℃, the characteristic peak intensities of CeO2 and Nb2O5 weakened, while the diffraction peaks of CeNbO4 became sharper, indicating a further increase in crystallinity. However, based on the performance data in Table 1, although CeNbO4 exhibited superior crystallinity at 1250℃, the SiC matrix had already undergone excessive oxidation, leading to film structure deterioration and decreased catalytic performance. Therefore, it can be inferred that there exists a performance inflection point between 1150℃ and 1250℃—a temperature range where CeNbO4 crystallinity continues to increase but matrix oxidation is not yet severe. Considering both the XRD phase evolution and performance results, 1050-1200℃ represents a suitable sintering temperature range that balances CeNbO4 formation with the integrity of the matrix structure.

[0049] The preparation method of this application is a one-step sintering method. The raw materials contain only CeO2 powder and Nb2O5 powder. XRD results show that CeNbO4 diffraction peaks, which are not present in the raw materials, appeared in the sintered product. The intensity of these diffraction peaks gradually increased with increasing sintering temperature, while the intensities of the diffraction peaks of CeO2 and Nb2O5 decreased accordingly. The above phase evolution law is consistent with the characteristics of solid-state reactions, which fully demonstrates that the CeNbO4 composite oxide phase is generated by an in-situ solid-state reaction of CeO2 and Nb2O5 during sintering, rather than being added externally after pre-synthesis.

[0050] The Nb-Ce-doped silicon carbide ceramic membrane prepared in this application can be used for ozone catalytic oxidation degradation of organic wastewater, especially for the ozone catalytic oxidation degradation of antibiotic wastewater or dye wastewater.

[0051] In this application, the catalytic activity of the Nb-Ce-doped silicon carbide ceramic film originates from a three-phase synergistic system: firstly, Ce on the CeO2 surface... 3+ The site can activate ozone molecules, promoting the decomposition of O3 to produce hydroxyl radicals (·OH) and superoxide radicals (·O2). -These reactive oxygen species possess strong oxidizing capabilities, capable of non-selectively mineralizing organic pollutants into CO2 and H2O. Secondly, the Nb2O5 surface has acidic sites, enabling it to adsorb negatively charged or lone-pair organic pollutant molecules (such as the carboxyl and piperazine groups in ciprofloxacin, and nitrogen-containing heterocycles in methylene blue) through acid-base interactions. This enriches pollutants on the catalyst surface, increasing local concentration and accelerating the catalytic oxidation reaction rate. Thirdly, CeNbO4, as a CeNbO4 composite oxide phase generated in situ from CeO2 and Nb2O5 at high temperatures, exhibits a unique electronic environment formed by the coexistence of Ce and Nb in its crystal structure. On one hand, the abundant oxygen vacancies in the CeNbO4 composite oxide phase provide additional activation sites for ozone molecules; on the other hand, the presence of the CeNbO4 composite oxide phase enhances the synergy between the acidity and redox capabilities of the catalyst surface, allowing adsorbed organic pollutants to be more efficiently attacked and degraded by reactive oxygen species.

[0052] The synergistic effect of the three phases mentioned above enables the Nb-Ce doped silicon carbide ceramic membrane prepared in this application to not only have higher initial catalytic activity in the process of catalytic ozone oxidation, but also, because the catalytic active components are embedded into the SiC matrix through sintering to form an integrated structure, the bonding force between the catalyst and the membrane matrix is ​​better than that of the surface loading method, and it is not easy to fall off and be lost under long-term operation and water scouring conditions.

[0053] Application Example 1: The application of the Nb-Ce doped silicon carbide ceramic membrane prepared in this application in the treatment of recalcitrant antibiotic wastewater (ciprofloxacin wastewater).

[0054] The Nb-Ce-doped silicon carbide ceramic membranes prepared in each embodiment and comparative example were placed in a membrane reactor; the reactor was heated and the temperature was controlled at 25°C, the transmembrane pressure at 0.5 bar, the ozone concentration at 4 ppm, and the ciprofloxacin concentration at 80 ppm to treat the refractory ciprofloxacin wastewater.

[0055] The test results of treating refractory ciprofloxacin wastewater with pure SiC ceramic membrane coupled with ozone and pure ozone were used as the performance reference baseline.

[0056] Application Example 2: Application of the Nb-Ce-doped silicon carbide ceramic membrane prepared in this application in the treatment of recalcitrant dye wastewater (methylene blue wastewater).

[0057] The Nb-Ce-doped silicon carbide ceramic membranes prepared in each embodiment and comparative example were placed in a membrane reactor. The reactor was heated and controlled at a temperature of 25°C, a transmembrane pressure of 0.5 bar, an ozone concentration of 4 ppm, and a methylene blue concentration of 100 ppm to treat recalcitrant methylene blue wastewater.

[0058] The test results of treating recalcitrant methylene blue wastewater with pure SiC ceramic membrane coupled with ozone and pure ozone were used as a performance reference baseline.

[0059] The performance test results of the above embodiments and comparative examples for treating ciprofloxacin wastewater and methylene blue wastewater are shown in Table 1.

[0060] Table 1 Comparison of Removal Rates of Ciprofloxacin and Methylene Blue See Figure 6-7 And as shown in Table 1: Example 1 (1150℃, Ce:Nb=2:1) ​​showed the best removal efficiency for ciprofloxacin and methylene blue. The removal rate of ciprofloxacin reached 98.52% after 30 minutes, while the removal rates of ciprofloxacin by pure SiC ceramic membrane coupled with ozone and pure ozone were similar, at 56.62% and 56.89%, respectively. The removal rate of methylene blue reached 97.85% after 60 minutes, while the removal rates of methylene blue by pure SiC ceramic membrane coupled with ozone and pure ozone were 43.14% and 11.27%, respectively. This demonstrates that the Nb-Ce-doped silicon carbide ceramic membrane has good ozone catalytic oxidation activity, and the treatment effect of the Nb-Ce-doped silicon carbide ceramic membrane coupled with ozone on ciprofloxacin wastewater is better than that on methylene blue wastewater.

[0061] Example 2 (sintering at 1050℃) showed removal rates of 82.46% for ciprofloxacin and 86.04% for methylene blue, significantly lower than Example 1 (1150℃). Figure 2 XRD analysis showed that the CeNbO4 composite oxide phase was not fully formed at 1050℃, resulting in an insufficient number of catalytic active sites and a decline in performance.

[0062] Comparative Example 1 (containing only CeO2, without Nb2O5) showed a ciprofloxacin removal rate of 94.39%, which was higher than the blank control but lower than the 98.52% of Example 1; the removal rate of methylene blue was 93.89%, also lower than Example 1. This indicates that although CeO2 has certain catalytic activity, when used alone, it lacks the acidic adsorption sites provided by Nb2O5 and the synergistic effect of the CeNbO4 composite phase, thus limiting its catalytic efficiency.

[0063] Comparative Example 2 (containing only Nb₂O₅, without CeO₂) achieved removal rates of 58.73% for ciprofloxacin and 15.31% for methylene blue, which were close to those of the blank control. This indicates that although Nb₂O₅ can provide acidic surface sites for adsorbing pollutants, it lacks CeO₂ when present alone. 3+ / Ce 4+ The ability of redox cycles to generate reactive oxygen species has extremely limited catalytic degradation capacity for pollutants. This result also demonstrates, from the opposite perspective, the central role of CeO2 in the catalytic system and the necessity of Ce-Nb complex.

[0064] Comparative Example 3 (sintered at 1250℃) showed removal rates of 64.12% for ciprofloxacin and 71.52% for methylene blue, indicating that when the sintering temperature exceeds 1200℃, the SiC matrix undergoes excessive oxidation, resulting in membrane structure deterioration, decreased porosity, and hindered ozone mass transfer to the membrane interior, thus reducing catalytic performance.

[0065] Comparative Example 4 (sintered at 900℃) was not feasible because the sintering temperature was too low, the membrane preform was not sufficiently densified, and the mechanical strength was insufficient, which could not meet the requirements of membrane separation operation.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. An Nb-Ce-doped silicon carbide ceramic film, characterized in that, The Nb-Ce-doped silicon carbide ceramic film uses silicon carbide as a substrate. The bulk phase of the substrate contains a cerium- and niobium-containing composite oxide phase formed by an in-situ solid-state reaction of cerium oxide and niobium oxide. The surface of the Nb-Ce-doped silicon carbide ceramic film has Ce... 3+ / Ce 4+ Redox pairs and oxygen vacancies.

2. The Nb-Ce-doped silicon carbide ceramic film as described in claim 1, characterized in that, The cerium- and niobium-containing composite oxide phase is a CeNbO4 composite oxide phase.

3. The Nb-Ce-doped silicon carbide ceramic film as described in claim 1, characterized in that, The cerium- and niobium-containing composite oxide phase is distributed on the particle surface and particle neck region of the matrix.

4. A method for preparing an Nb-Ce-doped silicon carbide ceramic film, characterized in that, Includes the following steps: Cerium oxide powder and niobium oxide powder are mixed with silicon carbide powder to obtain a mixed powder. The mixed powder is formed into a film preform; The preform is sintered at 1050-1200℃ in an oxidizing atmosphere, so that the oxides of cerium and niobium are in situ doped into the silicon carbide matrix and a composite oxide phase containing cerium and niobium is generated in situ. At the same time, the composite oxide phase containing cerium and niobium generates surface oxygen vacancies at the sintering temperature, thus obtaining the Nb-Ce doped silicon carbide ceramic film.

5. The method for preparing Nb-Ce-doped silicon carbide ceramic films as described in claim 4, characterized in that, The mixed powder also contains a pore-forming agent and a low-temperature binder.

6. The method for preparing Nb-Ce-doped silicon carbide ceramic films as described in claim 4, characterized in that, The oxide of cerium is cerium oxide, and the oxide of niobium is niobium oxide.

7. The method for preparing Nb-Ce-doped silicon carbide ceramic films as described in claim 4, characterized in that, The mass ratio of the cerium oxide powder to the niobium oxide powder is (1.5-2.5):

1.

8. The method for preparing Nb-Ce-doped silicon carbide ceramic films as described in claim 4, characterized in that, The step of forming the mixed powder into a preform includes adding a plasticizer and a solvent to the mixed powder, kneading it evenly, and then aging and extruding it to obtain a tubular preform.

9. The method for preparing Nb-Ce-doped silicon carbide ceramic films as described in claim 4, characterized in that, The oxidizing atmosphere is air.

10. The application of the Nb-Ce-doped silicon carbide ceramic membrane according to any one of claims 1 to 3 in the ozone catalytic oxidation degradation of organic wastewater.

Citation Information

Patent Citations

  • Alumina ceramic sintered body as well as preparation method and application thereof

    CN112979282A

  • Silicon carbide microreactor for ozone catalysis as well as preparation method and application of silicon carbide microreactor

    CN119306314A